Comparative planning and housing studies beyond taxonomy: a genealogy of the special programme for rehousing (Portugal) - Tulumello, S. (2019)
Recent European comparative studies in the fields of housing policy and spatial planning have been dominated by taxonomical and linear approaches, and by normative calls for convergence toward systems considered more ‘mature’ or ‘advanced’. In this article, we adopt a genealogical perspective and consider those cultures that are central to the shaping of policy. We set out a long-term exploration of the intersection between spatial planning and housing policy in Portugal and focus on the Special Programme for Rehousing (Programa Especial de Realojamento, PER), a programme that has had changing roles (from a financial instrument to a core component of policies of urban regeneration) in connection with political and planning cultures changing in time and space. In this way, we provide evidence of the limited capacity of taxonomic and linear approaches to describe planning and housing systems undergoing processes of change and, conversely, show the potential of genealogical research.